Evaluation of wind energy potential for different turbine models based on the wind speed data of Zabol region, Iran. (August 2017) - Pishgar-Komleh, S.H.; Akram, A.
Abstract: Adverse consequences arising from the use of fossil fuels on the environment has led mankind to introduce renewable sources of energy. Wind energy is one of the best alternatives (after hydropower) for fossil fuel energy in Iran. To calculate the wind energy potential in the Zabol district, Iran, wind speed values were taken from the meteorological station of the district during a 10-year period (2002–2011). The results showed that the average wind speed in the region is almost 6.5 m.s −1 . The lowest and highest wind speeds occur in cold and warm seasons, respectively. The diurnal wind speed analysis demonstrated that the fastest winds blow from 3 a.m. to 9 a.m. The assessment of wind energy potentiality was carried out with the help of Weibull and Rayleigh distributions. The yearly total power density and wind energy density were 424 W.m −2 and 3720 kW.h.m −2, respectively, which indicates that the Zabol city ranks in class 6 (which is a suitable area for wind turbine establishment). The wind rose diagram revealed that the dominant wind direction with the highest contribution in the region blows between 112.5° to 135°. Finally, the performance of different turbine models was done based on the Zabol wind speed data.